Common fixed point theorems via common limit range property in symmetric spaces under generalized Phi-contractions - Nashine, Hemant Kumar Kumar; Kadelburg, Zoran (Nonlinear Analysis: Modelling and Control, 2015)
The aim of this paper is to use common limit range property for a quadruple of non-self mappings for deriving common fixed point results under a generalized Φ-contraction condition in symmetric spaces. Some examples are given to exhibit different types of situations where these conditions can be used and to distinguish our results from the known ones. As an application, an existence result for certain systems of integral equations is presented.